Combined neuroimaging and gene expression analysis of the genetic basis of brain plasticity indicates across species homology. Issue 12 (22nd July 2014) - Dinai, Yonatan; Wolf, Lior; Assaf, Yaniv
Abstract Brain plasticity and memory formation depend on the expression of a large number of genes. This relationship had been studied using several experimental approaches and researchers have identified genes regulating plasticity through a variety of mechanisms. Despite this effort, a great deal remains unknown regarding the role of different genes in brain plasticity. Previous studies usually focused on specific brain structures and many of the genes influencing plasticity have yet to be identified. In this work, we integrate results of in vivo neuroimaging studies of plasticity with whole‐brain gene expression data for the study of neuroplasticity. Brain regions, found in the imaging study to be involved in plasticity, are first spatially mapped to the anatomical framework of the genetic database. Feature ranking methods are then applied to identify genes that are differentially expressed in these regions. We find that many of our highly ranked genes are involved in synaptic transmission and that some of these genes have been previously associated with learning and memory. We show these results to be consistent when applying our method to gene expression data from four human subjects. Finally, by performing similar experiments in mice, we reveal significant cross species correlation in the ranking of genes. In addition to the identification of plasticity related candidate genes, our results also demonstrate the potential of data integration approaches as a tool to link high level phenomena such as learning and memory to underlying molecular mechanisms. Hum Brain Mapp 35:5888–5902, 2014. © 2014 Wiley Periodicals, Inc.